Full-field experimental and numerical characterisation of a growing fatigue crack in a stainless steel. (April 2020) - Alshammrei, S.; Lin, B.; Tong, J.
Highlights: Full-field studies of a growing fatigue crack using DIC and FE. Integrated FE carried out using displacement data collected in situ from DIC. Critical strains at crack onset found to be dependent of measurement window size. Crack closure found to be of no impact on J-integral or strains during crack growth. Abstract: Full-field mechanical characterisation has been carried out for growing cracks under cyclic loading conditions using both Digital Image Correlation (DIC) and integrated finite element (FE) analysis. Compact tension specimens of a model material, stainless steel 316L, were used in the experiments, where the position of the crack tip and the evolution of the near-tip displacements and strains were tracked at selected observation points along the crack path. "Critical" strains at the advancing crack tip were captured at selected locations along the crack path. The influence of DIC data processing strategies and the choice of a characteristic length on the critical strain were examined. Potential attenuation effects behind the crack tip, commonly referred to as crack closure, were also investigated by evaluating the crack opening displacement (COD) at selected instances to the crack tip during the crack growth, where the experiment was interrupted to allow DIC measurements taken during a complete cycle. The impact of measured crack closure on the near-tip strains and crack driving force in terms of J-integral was assessed using both standard and integrated FE analysis.